Korozija kromita v kromitno magnezitnih gradivih - Mirtič, Breda (Kovine zlitine tehnologije, 1995)
Magnesia-chrome refractories are used for covering the thermally, mechanicallyand chemically most loaded parts of kiln where lining damages are also present. One of the distinguished causes of damage is the chromite corrosion in the brick. As the consequence of the insufficient protective coating magnesia-chrome lining is overheated. Too high working temperatures cause evaporating of the chromium oxide from the chromite grains. Investigations made on corroded magnesia-chrome bricks from the burning zoneof rotary cement kiln have shown that the melt full of calcium oxide and silica from the cement clinker has penetrated into the ining, filled the poresand caused the so called recrystallization of chromite.
Keywords: brick; opeka; gradiva; kromitno magnezitna gradiva; korozija; cementna peč; izparevanje